1998
DOI: 10.1111/j.1749-6632.1998.tb09682.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Glycosphinglipids in Neurological Disorders: Mechanisms of Immune Actiona

Abstract: Specific criteria that are required for understanding the significance of glycosphingolipid (GSL) antibodies, as well as mechanisms that may underlie the immunopathogenesis of these disorders, are proposed. These criteria are illustrated by describing the role of a unique family of acidic GSLs, the sulfated glucuronosyl glycolipids (SGGLs), in the pathogenic mechanisms of peripheral neuropathy with IgM paraproteinemia. High anti-SGGL antibody titers are detected in patients suffering from this disorder. It is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 130 publications
(157 reference statements)
2
30
0
Order By: Relevance
“…Furthermore, numerous studies have shown that antibodies can be found within neurons, which supports the feasibility of our approach; for example [2, 28, 32-35, 37, 47, 48, 54, 74, 82, 85, 102, 105, 127, 130, 131, 136]. The antibodies may be taken up into cells by pinocytosis (e.g., receptor-mediated endocytosis or fluid-phase endocytosis) [75].…”
Section: Mechanism Of Clearancesupporting
confidence: 75%
“…Furthermore, numerous studies have shown that antibodies can be found within neurons, which supports the feasibility of our approach; for example [2, 28, 32-35, 37, 47, 48, 54, 74, 82, 85, 102, 105, 127, 130, 131, 136]. The antibodies may be taken up into cells by pinocytosis (e.g., receptor-mediated endocytosis or fluid-phase endocytosis) [75].…”
Section: Mechanism Of Clearancesupporting
confidence: 75%
“…It is worth mentioning that our GSL preparation was completely free of the contaminating brain proteins (as determined by mass spectrometry following acid hydrolysis) that might stimulate the antibody production directed towards myelin proteins (26,27). High titer antibodies against GSLs, such as GM1, GD1a, GD1b, and LM1 have been a subject of intense interest in human demyelinating diseases in recent years (for review, see 28,29). High titer anti-GSL sera have been implicated in a wide variety of human peripheral autoimmune neuropathy and demyelinating diseases, such as lower motor neuron syndrome (30), multifocal motor neuropathy (31), acute motor axonal neuropathy and gammopathy (32,33), multiple sclerosis (34)(35)(36), GuillainBarre´syndrome (37,38), and the removal of the antibody from the patients' blood by plasmapheresis fosters clinical recovery (39).…”
Section: Resultsmentioning
confidence: 99%
“…Various anti-ganglioside antibodies have been reported in the sera of patients with Guillain-Barré Syndrome (GBS) or related disorders [11,16,17]. We present clinical features of two patients, one with AIDP and the second with CIDP, who were treated with plasma exchange.…”
Section: Introductionmentioning
confidence: 94%
“…In addition, the humoral immune response is involved with elevated levels of immunoglobulins (IgG and IgM) and complement deposition in the PNS [7,8]. Although some patients with CIDP have monoclonal gammopathies with high levels of IgM antibodies to PNS antigens, including myelin-associated glycoprotein (MAG) and sulfated glucuronyl paragloboside (SGPG) [9][10][11], the clinical symptoms of CIDP are different from that of other gammopathies [12].…”
Section: Introductionmentioning
confidence: 96%